1990
DOI: 10.1007/bf01257081
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1A receptor function in depression: effect of chronic amitriptyline treatment

Abstract: Hypothermic responses to 5-HT1A receptor activation by the selective ligand ipsapirone (IPS) were attenuated in depressed patients as compared to controls. Chronic treatment with amitriptyline (AMI) further impaired 5-HT1A-mediated hypothermia. The results indicate a subsensitive (presynaptic) 5-HT1A receptor and/or a defective post-receptor signalling pathway in depression and are consistent with the hypothesis that 5-HT1A receptors are down-regulated during AMI treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 10 publications
2
29
0
1
Order By: Relevance
“…The second possibility is that alterations in 5-HT 1A receptor function are functionally relevant to mood when they occur in the clinical (and neurobiological) context of depression but not in normal subjects. Blunted hypothermic (Lesch et al 1990c, Cowen et al 1994, ACTH and cortisol (Lesch et al 1990d;Meltzer and Maes 1994) responsiveness to 5-HT 1A receptor agonists, including ipsapirone, have been reported in depressed patients and a reduced hypothermic response to ipsapirone was observed following chronic antidepressant (amitriptyline) administration (Lesch et al 1990e). Further studies on the effect of SSRIs on 5-HT 1A receptor-mediated hypothermic and neuroendocrine responses in depressed patients are needed in order to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…The second possibility is that alterations in 5-HT 1A receptor function are functionally relevant to mood when they occur in the clinical (and neurobiological) context of depression but not in normal subjects. Blunted hypothermic (Lesch et al 1990c, Cowen et al 1994, ACTH and cortisol (Lesch et al 1990d;Meltzer and Maes 1994) responsiveness to 5-HT 1A receptor agonists, including ipsapirone, have been reported in depressed patients and a reduced hypothermic response to ipsapirone was observed following chronic antidepressant (amitriptyline) administration (Lesch et al 1990e). Further studies on the effect of SSRIs on 5-HT 1A receptor-mediated hypothermic and neuroendocrine responses in depressed patients are needed in order to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-HT 1A receptor system in particular has been implicated in the pathophysiology of depression, and antidepressant drug mechanisms. Depressed subjects showed blunted response to 5-HT 1A agonists in vivo and decreased 5-HT 1A receptor binding postmortem (29)(30)(31). Drevets et al (11,12) and Sargent et al (45) found reduced 5-HT 1A receptor binding potential in subjects with familial depression relative to controls in regions including raphe and mesiotemporal cortex.…”
Section: Introductionmentioning
confidence: 98%
“…Two recent neuroendocrine challenge studies using the 5-HT la agonist ipsapirone also lend support for differences in 5-HTla receptor function in MOD. The frrst study found that the hypo thermic response to ipsapirone was attenuated after amitriptyline treatment (Lesch et al 1990). The second study by the same group found a blunted ipsapirone induced adrenocorticotrophic hormone (ACTH) re sponse in patients with MOD compared to controls (Lesch et al 1991).…”
mentioning
confidence: 99%